Anatomical Closure of Left-to-Right Shunts in Premature Infants with Bronchopulmonary Dysplasia and Pulmonary Hypertension: A Cautionary Tale - Dereddy, Narendra R.; Chilakala, Sandeep R.; Rana, Divya (American Journal of Perinatology Reports, 2015)
Closure of a systemic to pulmonary shunt in premature infants with bronchopulmonary dysplasia may be beneficial, but in the presence of pulmonary hypertension is controversial. Here, we discuss two premature infants with pulmonary hypertension who developed acute pulmonary hypertensive crisis after closure of these shunts and hence advise caution.
Keywords: premature; chronic lung disease; pulmonary hypertension; patent ductus arteriosus